Dietary Inflammatory Index Is Associated With Inflammation in Japanese Men - Kotemori, Ayaka; Sawada, Norie; Iwasaki, Motoki; Yamaji, Taiki; Shivappa, Nitin; Hebert, James R.; Ishihara, Junko; Inoue, Manami; Tsugane, Shoichiro (Frontiers in Nutrition, 2021)
Background: Dietary components are known to affect chronic low-grade inflammation status. The dietary inflammatory index (DII®) was developed to measure the potential impact of a diet on an individual's inflammatory status, and it has been validated mainly in Western countries. Objective: This study aimed to examine the validity of the energy-adjusted DII (E-DIITM) using high-sensitivity C-reactive protein (hs-CRP) concentration in Japanese men and women. Methods: In total, 6,474 volunteers from a cancer-screening program (3,825 men and 2,649 women) completed a food frequency questionnaire (FFQ) and their hs-CRP concentrations were evaluated. E-DII scores were calculated on the basis of 30 food parameters derived from the FFQ. Higher E-DII scores reflect a greater pro-inflammatory potential of the diet. The associations between E-DII quartiles and hs-CRP concentration were assessed using regression models adjusted for age, body mass index, smoking status, and amount of physical activity. Results: Mean E-DII in men and women was + 0.62 ± 1.93 and −1.01 ± 2.25, respectively. The proportion of men and women who had hs-CRP concentration >3 mg/L was 4.7 and 3.1%, respectively. A significant positive association was observed between E-DII score and hs-CRP concentration in men; geometric mean of hs-CRP concentration in the lowest and highest E-DII quartiles was 0.56 mg/L and 0.67 mg/L (Ptrend < 0.01), respectively. The odds ratio (95% confidence interval) of having an elevated hs-CRP concentration (>3 mg/L) was 1.72 (1.10–2.67) in the highest E-DII quartile (Ptrend = 0.03) in men. However, no association was observed between E-DII score and hs-CRP concentration in women, except in those not taking prescription medications. Conclusions: DII was associated with inflammation status in Japanese men, but the association was limited in Japanese women.